Direct Ischemic Postconditioning After Carotid Endarterectomy in the Prevention of Postoperative Cerebral Ischemic Complications—Observational Case–Control Study. (15th November 2022) - Ilijevski, Nenad; Atanasijević, Igor; Lozuk, Branko; Gajin, Predrag; Matić, Predrag; Babić, Srđan; Sagić, Dragan; Unić-Stojanović, Dragana; Tanasković, Slobodan
Introduction: Ischemic postconditioning (IPCT) represents one of the several therapeutic strategies to attenuate ischemic reperfusion injury (IR) after carotid endarterectomy (CEA). We here present the first in-human study of IPCT in carotid surgery. Methods: The study represents an observational case-control study, with the data collected in our Institution carotid database. From December 2015 to December 2020, a total of 300 patients were included in our study; IPCT group consisted of 148 patients in whom ischemic postconditioning was performed while control group consisted of 152 patients in whom IPCT was not performed. Indications for IPCT technique were: severe unilateral internal carotid artery (ICA) stenosis (>90%), severe bilateral ICA stenosis (>80%), severe ICA stenosis (>80%) with contralateral ICA occlusion and ICA subocclusion. IPCT was performed by applying 6 cycles of 30 sec reperfusion (declamping of ICA)/30 sec ischemia (clamping of ICA) after finishing the procedure and initial declamping. Two groups of patients were compared in terms of occurrence of intrahospital and early postoperative stroke, TIA (transient ischemic attack) and neurologic morbidity. Results: Cumulative incidence of intrahospital postoperative stroke or TIA was significantly higher in the control group (5.3% vs 0.7%, P = .036). According to carotid plaque characteristics, patients in the IPCT group had significantly more frequent presence of heterogenous plaque, as well as ulcerated plaque, which was associated with the absence of postoperative stroke and significantly lower cumulative rate of TIA/stroke when compared to the control group (43.9% vs 8% and 47.3% vs 1.5%). During the follow-up period of 1 month after the surgery, there were no cases of stroke, TIA and deaths due to neurological causes in both groups of patients. Conclusion: Our results showed that IPCT significantly reduced the incidence of postoperative cerebral ischemic complications after CEA in high-risk patients for IR injury when compared to the control group.